Transcriptome Analysis and the Prognostic Role of NUDC in Diffuse and Intestinal Gastric Cancer. (31st May 2021) - Jeong, Sang-Ho; Park, Miyeong; Park, Sun Yi; Park, Jiho; Kim, Tae-Han; Lee, Young-Joon; Jung, Eun-Jung; Ju, Young-tae; Jeong, Chi-Young; Kim, Ju-Yeon; Ko, Gyung Hyuck; Kim, Minhye; et al.
Introduction: There have been few studies about gene differences between patients with diffuse-type gastric cancer and those with intestinal-type gastric cancer. The aim of this study was to compare the transcriptomes of signet ring cell gastric cancer (worst prognosis in diffuse-type) and well-differentiated gastric cancer (best prognosis in intestinal-type); NUDC was identified, and its prognostic role was studied. Materials and Methods: We performed next-generation sequencing with 5 well-differentiated gastric cancers and 3 of signet ring cell gastric cancer surgical samples. We performed gene enrichment and functional annotation analysis using the Database for Annotation, Visualization and Integrated Discovery bioinformatics resources. Immunohistochemistry was used to validate NUDC expression. Results: Overall, 900 genes showed significantly higher expression, 644 genes showed lower expression in signet ring cell gastric cancer than in well-differentiated gastric cancers, and there was a large difference in adhesion, vascular development, and cell-to-cell junction components between the 2 subtypes. We performed variant analysis and found 52 variants and 30 cancer driver genes, including NUDC. We analyzed NUDC expression in gastric cancer tissue and its relationship with prognosis. Cox proportional hazard analysis identified T stage, N stage, and NUDC expression as independent risk factors for survival ( P < 0.05). The overall survival of the NUDC-positive group was significantly higher (53.2 ± 0.92 months) than that of the NUDC-negative group (44.6 ± 3.7 months) ( P = 0.001) in Kaplan-Meier survival analysis. Conclusion: We found 30 cancer driver gene candidates and found that the NUDC-positive group showed significantly better survival than the NUDC-negative group via variant analysis.